Strategi Kebijakan: Integrasi Kurikulum Modern di Pesantren sebagai Pilar Transformasi Pendidikan Islam di Era 5.0 - Muh. Yahya (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy paper outlines that the transformation of Islamic education in the digital era requires Islamic boarding schools (pesantren) to integrate a modern curriculum without sacrificing traditional Islamic values. This study analyzes the policy strategy for integrating a modern curriculum in Islamic boarding schools as a response to the challenge of ensuring the relevance of graduates to the demands of the times. The study methodology uses a qualitative approach with USG (Urgency, Seriousness, Growth) analysis developed to identify problem priorities, root cause analysis using a fishbone diagram, and evaluation of policy alternatives based on William N. Dunn's criteria. Data were obtained through a study of educational policy documentation, institutional performance reports, and a review of academic literature. The analysis shows that the main problem lies in the absence of operational regulations that guide the integration of a modern curriculum in the Islamic boarding school education system. The study recommends the Minister of Religious Affairs Regulation on the Integration of a Modern Curriculum in Islamic Boarding Schools as the most strategic policy instrument to bridge tradition and modernity in Islamic education towards Indonesia Emas 2045.